Affect Heuristic and Influence of ‘Name’ in Investment Decisions of Nepalese Investors - Vaidya, Rashesh; Chitrakar, Bikram; Ghimire, Sanjeev (Journal of Economics and Management, 2024)
The study aims to investigate the presence of affect heuristics in investment decisions and analyze the influence of company and financial tool names in investment decisions. The framework of the Affect Heuristic Model was adapted to measure perceived risk and perceived benefit. Besides the impact of fluency, association and familiar names were tested to discover the level of perceived risk and perceived benefit during the investment decision. The research was conducted among 150 investors who invest in the Nepal Stock Exchange through an online form. The study indicates that Nepalese investors tend to rely on heuristic shortcuts, such as fluency, familiarity, and association, when assessing investment opportunities. They are notably influenced by affect ‘name’ heuristics, shaping their perceptions of benefits. Moreover, their perception of risk and benefit is more influenced by trends and superficial factors like glitz than past performance and corporate character. Local companies and well-known brands are favored due to the familiarity heuristic.